Valor nutricional, capacidade antioxidante e utilização de folhas de espinafre (Tetragonia tetragonoides) em pó como ingrediente de pão de forma. - Azevedo, Fátima de Lourdes Assunção Araújo de (2012)
Spinach is a dark green leafy vegetables in the diet that helps with the intake of vitamins, proteins, minerals, especially calcium and iron, and bioactive compounds not common in other plants. The objective of this research was to characterize the spinach Tetragonia tetragonoides, fresh and powdered (bleached and un bleached) on the content of nutrients, antinutritional and bioactive compounds, evaluating the effects of bleaching on these compounds, the antioxidant capacity of bioactive compounds and functional potential of spinach bleached powder as an ingredient in the formulation of bread. The powder of spinach leaves, subjected to bleaching, decreased concentrations of nutrients, antinutritional and bioactive compounds, compared to the same product is not bleached. The greatest losses were observed for iron (19,4 %), calcium (18,3 %), oxalic acid (36,4 %), phytic acid (33,5 %) and ascorbic acid (18,74 %). The reduction in bioactive compounds resulted in lower antioxidant capacity of spinach powder bleached, as assessed by FRAP methods and linoleic β-caroteno/ácido, however, this effect was not observed by the DPPH method, and spinach powder, subjected or not to bleaching, presented the same antioxidant power. When the spinach bleached powder was added to the formulation of the loaf of bread, the concentrations of 1 %, 2 % and 3 % was observed better sensory acceptability in the formulation of 3 % was noted that the other as the softness. This formulation showed a higher content of protein, calcium, iron and phosphorus than the control bread. Therefore, the use of spinach as an ingredient of bread can be a good alternative to inclusion of the hardwood vegetables in the diet, contributing to improved nutrition and presenting, in the form bleached, reduced antinutritional content.